Cauliflower for sale in Rovaniemi, Finland in June, 2018 - Campbell, Sandy (2018)
This cauliflower was for sale in the K Supermarket in Rovaniemi, Finland, near the Arctic Circle in June, 2018. It was priced at 3.49 Euros/kilo.